2009
DOI: 10.1111/j.1420-9101.2009.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Social cohesion among kin, gene flow without dispersal and the evolution of population genetic structure in the killer whale (Orcinus orca)

Abstract: In social species, breeding system and gregarious behavior are key factors influencing the evolution of large‐scale population genetic structure. The killer whale is a highly social apex predator showing genetic differentiation in sympatry between populations of foraging specialists (ecotypes), and low levels of genetic diversity overall. Our comparative assessments of kinship, parentage and dispersal reveal high levels of kinship within local populations and ongoing male‐mediated gene flow among them, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
124
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 48 publications
14
124
0
Order By: Relevance
“…The nuclear trees were based on relatively short, dispersed sequences, but several evolution models that account for rate variation across the sequence were applied and the trees consistently showed the same overall topology. The AT-rich tree again agreed with the overall topology, but grouped the offshores into the same lineage as the transients, a result that is consistent with inference from microsatellite DNA loci in Pilot et al (2010).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The nuclear trees were based on relatively short, dispersed sequences, but several evolution models that account for rate variation across the sequence were applied and the trees consistently showed the same overall topology. The AT-rich tree again agreed with the overall topology, but grouped the offshores into the same lineage as the transients, a result that is consistent with inference from microsatellite DNA loci in Pilot et al (2010).…”
Section: Discussionsupporting
confidence: 72%
“…The AT-rich tree (Supplementary Figure 2) again supported the broader topology, but the 'offshore' group clustered with the 'transients' . The observed discordance between the nuclear and mtDNA phylogenies has been noted earlier in the North Pacific (Pilot et al, 2010) and among North Atlantic ecotypes (Foote et al, 2009(Foote et al, , 2013) based on comparisons between mtDNA control region sequences and microsatellite DNA genotypes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, if gene flow upon secondary contact was primarily between the transient and offshore ecotypes (as suggested by Pilot et al, 2010), this would result in the offshores and transients sharing derived alleles and the correlation of allele frequencies at shared ancestral polymorphisms (Figure 1d), potentially changing the basal position of the transients.…”
mentioning
confidence: 99%
“…However, intermediate lineages (such as those in the North Atlantic) and further complexity in the North Pacific and Southern Oceans would have the same representation in each of the four models, and therefore their omission may not represent a bias. We also allow for free association (very wide priors for migration rate) between transients and offshores after secondary contact, giving full potential to the connectivity illustrated in Figure 1d of Foote and Morin (2015), and as may be suggested by overlapping clusters in the PCA plot based on 16 microsatellite DNA loci in Pilot et al (2010); though not as clearly from the kinship analyses in that paper. However, similar overlap between transients and offshores is not seen for FCA plots based on 2934 neutral SNPs in Moura et al (2014a), and Hoelzel et al (2007) found roughly equivalent levels of gene flow when comparing all North Pacific ecotypes for both long-term and post-division migration estimates (always close to one migrant per generation).…”
mentioning
confidence: 99%